2005
DOI: 10.1159/000087670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Obstructive Pulmonary Disease according to BTS, ERS, GOLD and ATS Criteria in Relation to Doctor’s Diagnosis, Symptoms, Age, Gender, and Smoking Habits

Abstract: Background: Guidelines and standards for diagnosis and management of chronic obstructive pulmonary disease (COPD) have been presented by different national and international societies, but the spirometric criteria for COPD differ between guidelines. Objectives: To estimate prevalence of COPD using the guidelines of the British Thoracic Society (BTS), the European Respiratory Society (ERS), the Global Initiative for Chronic Obstructive Lung Disease (GOLD), and the American Thoracic Society (ATS). Further, to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 64 publications
11
105
2
1
Order By: Relevance
“…(1,2) Several studies have shown that the proportion of COPD cases tends to increase with age. (7)(8)(9) For statistical analysis, we used the Statistical Package for the Social Sciences, version 15 (SPSS Inc., Chicago, IL, USA), logistic regression analysis being performed and ORs being calculated. The level of statistical significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) Several studies have shown that the proportion of COPD cases tends to increase with age. (7)(8)(9) For statistical analysis, we used the Statistical Package for the Social Sciences, version 15 (SPSS Inc., Chicago, IL, USA), logistic regression analysis being performed and ORs being calculated. The level of statistical significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, asthma occurs in approximately 8–10% of the population [2]. According to various diagnostic criteria, another Swedish study found that COPD occurred in 8% (British Thoracic Society criteria), 14% (ERS or Global Initiative for Chronic Obstructive Lung Disease [GOLD] criteria), or 12% (American Thoracic Society clinical criteria) of the population [3]. …”
Section: Introductionmentioning
confidence: 99%
“…As there is a normal age-related decline of lung function, 27 using a fixed FEV 1 /FVC threshold of 70%, although it is a pragmatic approach, may lead to over-diagnosis of COPD in the elderly. 15,[28][29][30] According to some authors, post-bronchodilator GOLD stage II is a practical threshold for identifying clinically relevant disease. 31 Given the fact that, in our sample, the majority of participants had moderate or higher obstruction, it is unlikely that prevalence of obstructive pattern was overestimated due to misclassification of healthy elderly individuals as having obstruction.…”
Section: Discussionmentioning
confidence: 99%